Marital splits and income changes over the longer term - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2008)
What happens to peoples incomes when their or their parents marital union dissolves? Using data from waves 1-14 (survey years 1991-2004) of the British Household Panel Survey, I show that marital splits are associated with short-term declines in income for separating wives and children relative to separating husbands, but the size of the decline has declined over time markedly for women with children and this most likely reflects the effects of secularly rising employment rates and, related, the introduction of Working Families Tax Credit in 1998. Analysis of income trajectories suggests that in the five years following a marital split, incomes for separating wives recover but not to their previous levels.
Keywords: 330